Trust Over Use: Examining the Roles of Media Use and Media Trust on Misperceptions in the 2016 US Presidential Election. Issue 5 (3rd September 2021) - Hutchens, Myiah J.; Hmielowski, Jay D.; Beam, Michael A.; Romanova, Ekaterina
ABSTRACT: This study examines both the antecedents and consequences of partisan misperceptions during the 2016 US Presidential election using a three-wave panel study collected by YouGov. Both cross-sectionally and over time, this study examines the relationships between both partisan media use and media trust on misperceptions. In addition, it examines the relationship between misperceptions and avoiding partisan media sources that could correct partisan misperceptions. The results suggest that partisan media use and trust in partisan media outlets are related to beliefs in misperceptions that favor the in-party. However, trust in in-party partisan media outlets is a better predictor of holding misperceptions and subsequent out-party media avoidance than actual partisan media use.